Site index curves for natural Aleppo pine forests in the central Ebro valley (Spain) - Rojo-Alboreca, Alberto; Cabanillas-Saldaña, Ana María; Barrio-Anta, Marcos; Notivol-Paíno, Eduardo; Gorgoso-Varela, José Javier (Instituto de Ecología, A.C., 2017)
Site index curves were created for natural Aleppo pine (Pinus halepensis Mill.) stands in the Ebro Valley (northeastern Spain). Data were obtained from 54 felled dominant trees. The Generalized Algebraic Difference Approach (GADA) was used to fit 11 equations with a longitudinal data structure that included all possible growth intervals. Three statistical criteria were used for model comparison: root mean square error (RMSE), adjusted coefficient of determination (R2adj) and Akaike’s information criterion (AIC). Graphical evaluation of the data (plots of observed against predicted values and of residuals against predicted values) was also conducted. In addition, the root mean square error (RMSE) was plotted against age. Finally, fitted site index curves for different site qualities were superimposed on the profile plots of the stems analysed. The best reference age (60 years) was calculated from the relative error in the dominant height prediction. The Hossfeld IV model proved the most suitable for representing site index in the study area. Furthermore, only three site index curves (6, 10 and 14 m at 60 years) were suitable for classifying the entire study area because of the low productivity of the stands. These were compared with other site index curves developed for Spain and other countries, for the natural range of distribution of the species. Specific site index curves must be created for the study area, because the existing qualities and growth patterns are not well-represented in other models.